Survival and growth of catfish Pangasionodon sp. larvae fed on vitamin C-enriched Artemia - Setiawati, Mia; Putri, Darina; Jusadi, Dedi (Indonesian Society of Scientific Aquaculture (ISSA), 2013)
ABSTRACT The research was conducted to evaluate effect of the administration of Artemia enriched with vitamin C on the survival, total body length, and average body weight of Pangasionodon sp. larvae. Artemia were enriched with either 0, 50, 100, or 150 mg/L vitamin C immersed in the culture medium for 13 hours. Two days old larvae were fed on enriched Artemia 12 times/day for seven days. At the end of feeding experiment, it was found that fish fed on Artemia enriched with 100 mg/L culture medium had the highest survival, total length and body weight, respectively 76.17±12.78%, 1.63±0.34 cm, and 20.6±3.8 mg. Keywords: survival, growth, Artemia, vitamin C, catfish, Pangasionodon sp. ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh Artemia yang diperkaya dengan vitamin C dosis berbeda terhadap kelangsungan hidup, panjang total, dan bobot tubuh larva ikan patin Pangasionodon sp. Pada penelitian ini, Artemia diperkaya dengan vitamin C dosis 0, 50, 100, atau 150 mg/L media pengayaan. Larva yang berumur dua hari diberi pakan Artemia hasil pengayaan sebanyak 12 kali sehari selama tujuh hari masa pemeliharaan. Pada akhir percobaan, didapatkan bahwa larva ikan yang diberi Artemia diperkaya vitamin C dosis 100 mg/L media pengayaan memberikan kelangsungan hidup 76,17±12,78%, panjang total 1,63±0,34 cm, dan bobot tubuh paling tinggi 20,6±3,8 mg. Kata kunci: kelangsungan hidup, pertumbuhan, Artemia, vitamin C, ikan patin, Pangasionodon sp.